All the President's men ; Looking back at the Cory years ; Covering the presidency [videorecording]. - Aquino, Corazon Cojuanco 1933-; Lazaro, Cheche; Ramos, Fidel Valdez 1928- (The Probe Team, 1993)
A look at the men who occupy major Cabinet positions in the administration of Fidel Ramos and Corazon Aquino; the men in media tasked to cover the President; and the members of the Presidential Coverage Team, Radio Television Malacanang tell their story.